Eudaimonia, Faith (Pistis), and Truth (Aletheia): Greek Roots and the Construction of Personal Meaning. Issue 1 (2nd January 2017) - Potter, Brent
Abstract : Reflections regarding the construction of personal meaning are considered from the perspectives of phenomenology, psychoanalysis, and ancient Greek thought. The notion of eudaimonia is elucidated as a function of faith ( pistis ) and truth ( aletheia ) as these concepts emerge in history, and in the phenomenology of Martin Heidegger and the psychoanalysis of Wilfred Bion. This view challenges current positive psychology interpretations of eudaimonia as happiness or well-being. Ways of knowing and being in the unknown (i.e., negative capability) are accented as important aspects of personal meaning and as genuine modes of relatedness and wellness, as opposed to rigidity and sensibilities of certitude.